Thymoquinone in the clinical treatment of cancer: Fact or fiction? - AbuKhader, Majed M. (Pharmacognosy Reviews)
Thymoquinone (TQ) is the bioactive phytochemical constituent of the seeds oil of Nigella sativa. In vitro and in vivo research has thoroughly investigated the anticancer effects of TQ against several cancer cell lines and animal models. As a result, a considerable amount of information has been generated from research thus providing a better understanding of the anti‑proliferating activity of this compound. Therefore, it is appropriate that TQ should move from testing on the bench to clinical experiments. The purpose of this review is to highlight the potential of TQ as an anticancer agent and the chances of this compound in the clinical treatment of cancer, with special attention on breast cancer treatment.
Keywords: Breast cancer; drug delivery; pharmacokinetics; thymoquinone